Silicon-modified hydrofining catalyst as well as preparation method and application thereof
By introducing silicon modified components into the hydrodesulfurization catalyst, a silicon modified hydrorefining catalyst is formed, which solves the problems of insufficient catalytic activity and high preparation cost, and achieves higher catalytic activity and lower production costs, and is suitable for the cleaning processing of inferior raw oils.
Patent Information
- Application Number
- CN202311220927.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-20
AI Technical Summary
When existing hydrodesulfurization catalysts treat inferior raw oil, they lack catalytic activity and are difficult to meet the needs of cleaning oil production. At the same time, there are problems of organic solvent consumption and high cost during the traditional preparation process.
Silicon modified hydrorefining catalyst is used, which consists of Group VIB metal elements as the main active metal component and Group VIII metal elements as the co-active metal component, and silicon modified components are introduced to circumvent the use of organic alcohols or acidic water through a simple and effective preparation method, and reduce production costs.
The catalyst's hydrodesulfurization and hydrodenitrogenation reaction activities are improved, the dispersion and microstructure of the active metal are improved, the production cost is reduced, and the processing needs of inferior raw oils are adapted.
Smart Images

Figure CN119680561A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of petrochemical industry, and in particular to a silicon-modified hydrorefining catalyst, a preparation method thereof, and applications thereof. Background Art
[0002] Hydrodesulfurization, a crucial process in oil processing, is a key technology for producing clean oils, and its core lies in the development of hydrogenation catalysts. After years of development, the commonly used hydrodesulfurization catalysts in industry have evolved into traditional supported Co(Ni)Mo(W) sulfide catalyst systems, with Mo and / or W as the primary active metal components and Co and / or Ni as co-active metal components. To address the conflict between declining crude oil quality and the need to upgrade to cleaner oils, the development of supported Co(Ni)Mo(W) catalysts with higher activity and stability is a key goal for ensuring the future production of clean oils.
[0003] After extensive research, the development strategy for highly active supported Co(Ni)Mo(W) catalysts has become increasingly clear. These strategies mainly include improving the dispersion of active metals, adjusting the acidity of the catalyst, and regulating the micromorphology of active species on the catalyst or the metal-support interaction (MSI).
[0004] CN102049270B discloses a catalyst using carbon and silicon oxide modified alumina as a carrier, K and P oxides as promoters, and Co and Mo oxides as active metal components for selective hydrodesulfurization of gasoline.
[0005] CN102335612B discloses a supported Co-Mo catalyst using silicon oxide-alumina as a carrier and alkaline earth metal oxide and phosphorus oxide as additives, which is used for selective hydrodesulfurization of low-quality FCC gasoline.
[0006] CN103316687B discloses a catalyst using a composite oxide of two or three of TiO2, SiO2, and Al2O3 as a carrier and a combination of two or three metals of Co, Mo, Ni, and W as an active metal component for deep hydrodesulfurization of diesel.
[0007] CN101058748B discloses a catalyst whose carrier is a composite oxide of titanium dioxide and silicon dioxide modified by phosphorus or HY molecular sieve, and whose active components are a combination of at least two metals among cobalt, molybdenum, nickel and tungsten. The catalyst is subjected to hydrorefining treatment on catalytic cracking diesel, which can effectively achieve deep desulfurization, denitrogenation and dearomatization of diesel.
[0008] CN102784653B discloses a catalyst having a carrier composed of aluminum oxide, silicon oxide, and magnesium oxide, an active component composed of WO3 and NiO or MoO3 and NiO, and containing an additive composed of K2O and Ga2O3, for use in coal tar hydrogenation to produce clean fuel oil.
[0009] Although SiO2 can be used as a promoter or carrier in hydrorefining catalyst applications, the introduction of Si is mostly done through mechanical mixing, that is, direct mixing of silica sol, silicic acid, or SiO2 powder with oxides such as Al2O3 or TiO2. This often causes SiO2 to easily agglomerate and unevenly distribute on the catalyst, with limited control over the carrier's surface properties. While catalyst activity can be improved, it is still insufficient and difficult to adapt to the increasingly inferior raw material processing needs of the future. Modifying catalysts with Si through sol-gel methods or organic solution impregnation methods has problems such as a cumbersome preparation process and the consumption of organic solutions (such as methanol, ethanol, etc.), which leads to increased catalyst costs. Summary of the Invention
[0010] The purpose of the present disclosure is to provide a silicon-modified hydrorefining catalyst and a preparation method and application thereof, which can simply prepare the silicon-modified hydrorefining catalyst and the catalyst has high catalytic activity.
[0011] In order to achieve the above-mentioned objectives, the first aspect of the present disclosure provides a silicon-modified hydrotreating catalyst, which, based on the total weight of the silicon-modified hydrotreating catalyst, comprises 15 to 40 weight percent of a main active metal component, 2 to 12 weight percent of a co-active metal component, 5 to 20 weight percent of a silicon-modified component, and 45 to 70 weight percent of a carrier; wherein the main active metal component and the co-active metal component are calculated in the form of metal oxides, and the silicon-modified component is calculated in the form of SiO2; the main active metal component is selected from one or more metal elements of Group VIB, and the co-active metal component is selected from one or more metal elements of Group VIII; and the carrier comprises alumina.
[0012] Optionally, the main active metal component includes oxides of one or both metal elements selected from Mo and W; and the auxiliary active metal component includes oxides of one or both metal elements selected from Ni and Co.
[0013] Optionally, the total acid content of the silicon-modified hydrorefining catalyst measured by pyridine infrared at 150° C. is 120 to 160 μmol / g;
[0014] Preferably, the silicon-modified hydrorefining catalyst comprises acid centers and Lewis acid centers, among which Acid center content 2 to 15 μmol / g; further preferably, The ratio of acid center content to Lewis acid center content is 1:10 to 50;
[0015] Optionally, the BET specific surface area of the silicon-modified hydrorefining catalyst is 200 to 300 m 2 / g, pore volume of 0.3~0.5cm 3 / g.
[0016] A second aspect of the present disclosure provides a method for preparing a silicon-modified hydrorefining catalyst, comprising the following steps:
[0017] S1. Mixing a main active metal component precursor, a co-active metal component precursor, a silicon-modified component precursor, water, and an alumina precursor, and performing an aging treatment to obtain a catalyst intermediate; wherein the metal element of the main active metal component precursor is selected from one or more metal elements of Group VIB, the metal element of the co-active metal component precursor is selected from one or more metal elements of Group VIII, and the silicon-modified component precursor is selected from one or more hydrolyzable silicon-containing compounds;
[0018] S2. Mixing the catalyst intermediate with an extrusion aid and a binder, and performing molding and calcining processes.
[0019] Optionally, in step S1, the weight ratio of the main active metal component precursor: the auxiliary active metal component precursor: the silicon-modified component precursor: water: the alumina precursor is 0.1-2: 0.02-1.5: 0.1-3: 1-4: 1; preferably 0.15-0.8: 0.05-0.7: 0.15-1.0: 2-3.5: 1.
[0020] Optionally, the main active metal component precursor is selected from one or more of a molybdenum metal precursor and a tungsten metal precursor; preferably, the molybdenum metal precursor is selected from one or more of sodium molybdate, ammonium molybdate, molybdenum chloride and molybdic acid, preferably ammonium molybdate; the tungsten metal precursor is selected from one or more of ammonium metatungstate, phosphotungstic acid and silicotungstic acid, preferably ammonium metatungstate and / or phosphotungstic acid;
[0021] The co-active metal component precursor is selected from one or more of a nickel metal precursor and a cobalt metal precursor; preferably, the nickel metal precursor is selected from one or more of nickel nitrate, basic nickel carbonate and nickel sulfate, preferably basic nickel carbonate and / or nickel nitrate; the cobalt metal precursor is selected from one or more of cobalt sulfate, cobalt carbonate, cobalt oxalate and cobalt nitrate, preferably cobalt nitrate and / or cobalt oxalate;
[0022] The silicon-modified component precursor is selected from one or more of silicon tetrachloride, methyl silicate, silicon acetate, tetraethyl silicate, propyl orthosilicate, tetraisopropyl orthosilicate and tetrabutyl silicate; preferably selected from one or more of tetraethyl silicate, propyl orthosilicate and tetrabutyl silicate.
[0023] The alumina precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide and aluminum nitrate; preferably pseudo-boehmite.
[0024] Optionally, in step S1, the aging treatment conditions include: aging at 0-40°C for 15-30h;
[0025] Optionally, the method further comprises: drying the product obtained by the aging treatment at 80-160° C. for 4-12 hours.
[0026] Optionally, in step S2, the calcination treatment conditions include: calcination at 300-700° C. for 3-10 hours; the calcination atmosphere is one or more of air, nitrogen, oxygen, argon and water vapor;
[0027] Optionally, before the calcination process, the product obtained by the molding process is dried at 80-160° C. for 4-12 hours.
[0028] A third aspect of the present disclosure provides a silicon-modified hydrorefining catalyst prepared according to the method described in the second aspect of the present disclosure.
[0029] The fourth aspect of the present disclosure provides the use of the silicon-modified hydrorefining catalyst described in the first and third aspects of the present disclosure in a feedstock oil hydrorefining reaction.
[0030] Optionally, the feedstock oil hydrorefining reaction comprises the following steps:
[0031] Under hydrogen conditions, the raw oil is brought into contact with the silicon-modified hydrorefining catalyst to carry out a hydrorefining reaction;
[0032] Optionally, the conditions of the hydrofining reaction include: reaction temperature of 260-380°C; hydrogen pressure of 4-10 MPa; hydrogen-oil volume ratio of 300-800:1; raw oil mass space velocity of 0.5-6h -1 ;
[0033] Optionally, the feedstock oil is selected from gasoline and / or diesel fractions;
[0034] Preferably, the feedstock oil hydrorefining reaction further comprises the following step: performing a sulfurization treatment on the silicon-modified hydrorefining catalyst before carrying out the hydrorefining reaction.
[0035] Through the above technical solution, the present disclosure provides a silicon-modified hydrorefining catalyst and its preparation method and application. The silicon-modified hydrorefining catalyst uses a VIB group metal element as the main active metal component and a VIII group metal element as the auxiliary active metal component, and introduces a silicon-modified component. The preparation method is simple and effective, and can effectively avoid the use of organic alcohols or acidic water in the traditional preparation process, thereby reducing production costs. At the same time, the silicon-modified hydrorefining catalyst can promote the uniform dispersion of Si species on the catalyst. The introduction of Si can adjust the distribution of acidic centers on the catalyst surface, improve the interaction between the active metal and the carrier, enhance the dispersibility of the active metal, optimize the microscopic stacking structure of the active species, and obtain a catalyst with a "surface microsphere structure", so that the catalyst's hydrodesulfurization and hydrodenitrogenation reaction activity is significantly improved.
[0036] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following detailed description, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0038] Figure 1 This is a SEM image of the silicon-modified hydrorefining catalyst prepared in Example 1. DETAILED DESCRIPTION
[0039] The following describes the specific embodiments of the present disclosure in detail. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure and are not intended to limit the present disclosure.
[0040] A first aspect of the present disclosure provides a silicon-modified hydrorefining catalyst, which comprises, based on the total weight of the silicon-modified hydrorefining catalyst, 15 to 40 wt% of a main active metal component, 2 to 12 wt% of a co-active metal component, 5 to 20 wt% of a silicon-modified component, and 45 to 70 wt% of a carrier; wherein the main active metal component and the co-active metal component are calculated in the form of metal oxides, and the silicon-modified component is calculated in the form of SiO2; the main active metal component is selected from one or more metal elements of Group VIB, and the co-active metal component is selected from one or more metal elements of Group VIII; and the carrier comprises alumina.
[0041] The present disclosure provides a silicon-modified hydrorefining catalyst, in which a VIB group metal element is used as the main active metal component and a VIII group metal element is used as the auxiliary active metal component, and a silicon-modified component is introduced. The preparation method is simple and effective, and can effectively avoid the use of organic alcohols or acidic water in the traditional preparation process, thereby reducing production costs. At the same time, the silicon-modified hydrorefining catalyst can promote the uniform dispersion of Si species on the catalyst. The introduction of Si can adjust the distribution of acidic centers on the catalyst surface, improve the interaction between the active metal and the carrier, enhance the dispersibility of the active metal, optimize the microscopic stacking structure of the active species, and obtain a catalyst with a "surface microsphere structure", so that the catalyst's hydrodesulfurization and hydrodenitrogenation reaction activity is significantly improved.
[0042] In a preferred embodiment, based on the total weight of the silicon-modified hydrorefining catalyst, the silicon-modified hydrorefining catalyst comprises 18-35% by weight of the primary active metal component, 4-10% by weight of the co-active metal component, 8-15% by weight of the silicon-modified component, and 55-70% by weight of the support. The silicon-modified hydrorefining catalyst with an optimized composition provided by this embodiment exhibits higher hydrodesulfurization and hydrodenitrogenation reaction activity.
[0043] In a specific embodiment, the main active metal component includes oxides of one or both metal elements selected from Mo and W; the auxiliary active metal component includes oxides of one or both metal elements selected from Ni and Co.
[0044] In a preferred embodiment, the total acid content of the silicon-modified hydrorefining catalyst measured by pyridine infrared at 150°C is 120 to 160 μmol / g;
[0045] Preferably, the silicon-modified hydrorefining catalyst comprises acid centers and Lewis acid centers, among which Acid center content 2 to 15 μmol / g; further preferably, The ratio of the acid center content to the Lewis acid center content is 1:10-50.
[0046] In one embodiment, the BET specific surface area of the silicon-modified hydrorefining catalyst is 200 to 300 m 2 / g, pore volume of 0.3~0.5cm 3 / g.
[0047] A second aspect of the present disclosure provides a method for preparing a silicon-modified hydrorefining catalyst, comprising the following steps:
[0048] S1. Mixing a main active metal component precursor, a co-active metal component precursor, a silicon-modified component precursor, water, and an alumina precursor, and performing an aging treatment to obtain a catalyst intermediate; wherein the metal element of the main active metal component precursor is selected from one or more metal elements of Group VIB, the metal element of the co-active metal component precursor is selected from one or more metal elements of Group VIII, and the silicon-modified component precursor is selected from one or more hydrolyzable silicon-containing compounds;
[0049] S2. Mixing the catalyst intermediate with a forming aid, and performing forming and calcining treatments.
[0050] In the method for preparing a silicon-modified hydrorefining catalyst provided by the present disclosure, water is used as a solvent, which can effectively avoid the use of organic alcohols or acidic water in the traditional preparation process and reduce production costs; and the present disclosure uses a hydrolyzable silicon-containing compound as a silicon-modified component precursor to prepare a silicon-modified hydrorefining catalyst together with a main active metal component precursor, an auxiliary active metal component precursor and an alumina precursor. The silicon-containing compound precursor can be hydrolyzed in situ, which is conducive to the uniform dispersion of silicon species in the catalyst, strengthens the electronic interaction between the active metal and the silicon species, puts the active metal in an electron-depleted state, promotes the adsorption of active intermediate species on the active metal surface, and at the same time modulates the interaction force between the active metal and the carrier, improves the dispersibility of the active metal and the microstructure of the active species, and significantly improves the hydrodesulfurization and hydrodenitrogenation reaction activities of the catalyst.
[0051] In one embodiment, in step S1, the weight ratio of the main active metal component precursor: the auxiliary active metal component precursor: the silicon modified component precursor: water: the alumina precursor is 0.1-2: 0.02-1.5: 0.1-3: 1-4:1.
[0052] In a preferred embodiment, in step S1, the weight ratio of the main active metal component precursor: the co-active metal component precursor: the silicon-modified component precursor: water: the alumina precursor is 0.15-0.8: 0.05-0.7: 0.15-1.0: 2-3.5: 1. Catalyst preparation based on the optimized raw material weight ratios defined in this embodiment can yield a silicon-modified hydrorefining catalyst with improved catalytic performance.
[0053] In a specific embodiment, the main active metal component precursor is selected from one or more of a molybdenum metal precursor and a tungsten metal precursor; preferably, the molybdenum metal precursor is selected from one or more of sodium molybdate, ammonium molybdate, molybdenum chloride and molybdic acid, preferably ammonium molybdate; the tungsten metal precursor is selected from one or more of ammonium metatungstate, phosphotungstic acid and silicotungstic acid, preferably ammonium metatungstate and / or phosphotungstic acid;
[0054] The co-active metal component precursor is selected from one or more of a nickel metal precursor and a cobalt metal precursor; preferably, the nickel metal precursor is selected from one or more of nickel nitrate, basic nickel carbonate and nickel sulfate, preferably basic nickel carbonate and / or nickel nitrate; the cobalt metal precursor is selected from one or more of cobalt sulfate, cobalt carbonate, cobalt oxalate and cobalt nitrate, preferably cobalt nitrate and / or cobalt oxalate;
[0055] The alumina precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide and aluminum nitrate; preferably pseudo-boehmite.
[0056] In a preferred embodiment, the silicon-modified component precursor is selected from one or more of silicon tetrachloride, methyl silicate, silicon acetate, tetraethyl silicate, propyl orthosilicate, tetraisopropyl orthosilicate and tetrabutyl silicate; preferably, it is selected from one or more of tetraethyl silicate, propyl orthosilicate and tetrabutyl silicate.
[0057] In one embodiment, a solution of the main active metal component precursor and the auxiliary active metal component precursor can be prepared with water. This solution, along with the silicon-modified component precursor, can then be dropwise added to the alumina precursor. The solution is then stirred and mixed, and then aged. Conventional equipment and conditions can be used for stirring and mixing to ensure uniform mixing of the raw materials.
[0058] In one embodiment, in step S1, the aging treatment conditions include: aging at 0-40° C. for 12-24 hours.
[0059] In one embodiment, the method further comprises: drying the product obtained by the aging treatment at 80-160° C. for 4-12 hours.
[0060] In a specific embodiment, in step S2, the molding process includes extrusion molding and reverse molding, preferably extrusion molding. The specific process and apparatus of extrusion molding are well known to those skilled in the art.
[0061] In one embodiment, the molding aid includes an extrusion aid and a binder;
[0062] The extrusion aid is selected from one or more of starch, sesbania powder, polyethylene glycol and methyl cellulose; preferably, the amount of the extrusion aid added is 1 to 10% by weight, preferably 3 to 8% by weight, based on the total weight of the components;
[0063] The binder is selected from one or more of nitric acid, citric acid, tartaric acid, oxalic acid and oxalic acid; preferably, the addition amount of the binder is 1 to 10 weight %, preferably 3 to 8 weight %, based on the total weight of all components.
[0064] The reagents used in the present disclosure can be purchased through conventional channels or prepared by known methods.
[0065] In one embodiment, the catalyst product obtained by the shaping process may have a strip shape, a clover shape, a granular shape, or a toothed ball shape.
[0066] In one embodiment, in step S2, the calcination treatment conditions include: calcination at 300-700° C. for 3-10 hours; the calcination atmosphere is one or more of air, nitrogen, oxygen, argon and water vapor;
[0067] Optionally, before the calcination process, the product obtained by the molding process is dried at 80-160° C. for 4-12 hours.
[0068] During the preparation of the catalyst, each step can be carried out using conventional equipment in the art.
[0069] A third aspect of the present disclosure provides a silicon-modified hydrorefining catalyst prepared according to the method described in the second aspect of the present disclosure.
[0070] The fourth aspect of the present disclosure provides use of the silicon-modified hydrorefining catalyst described in the first aspect or the third aspect in a feedstock oil hydrorefining reaction.
[0071] In one embodiment, the process comprises the following steps: contacting the crude oil with a silicon-modified hydrorefining catalyst under hydrogen conditions to carry out a hydrorefining reaction.
[0072] In one embodiment, the conditions of the hydrofining reaction include: reaction temperature of 260-380°C; hydrogen pressure of 4-10 MPa; hydrogen-oil volume ratio of 300-800:1; raw oil mass space velocity of 0.5-6h -1 ;
[0073] Optionally, the feedstock oil is selected from gasoline and / or diesel fractions.
[0074] In the present disclosure, the silicon-modified hydrotreating catalyst is subjected to a sulfurization treatment before the hydrotreating reaction is performed.
[0075] In a preferred embodiment, the temperature of the sulfurization treatment is 200-500°C, the pressure is 0.1-10 MPa, the time of the sulfurization treatment is 1-60 hours, and the liquid hourly space velocity is 0.1-20 hours. -1 , the hydrogen-to-oil volume ratio is 100-800.
[0076] The present disclosure is further described in detail below through examples. The raw materials used in the examples are all commercially available. The performance tests were performed using instruments commonly used in the field.
[0077] The methods for determining and calculating the total content of the oxides of the active component metals in the catalyst are well known in the art, specifically including XRF and ICP methods.
[0078] The test method for acid content includes pyridine infrared method.
[0079] The BET specific surface area of the sample was determined by nitrogen physical adsorption at low temperature.
[0080] The SEM test instrument for the samples is a Quanta F20 scanning electron microscope.
[0081] Example 1
[0082] (1) Take 6.05g of ammonium metatungstate and 3.89g of nickel nitrate and dissolve them in 54.72g of deionized water to prepare a mixed impregnation solution. Take another 6.94g of tetraethyl silicate and 17.10g of pseudo-boehmite for later use. Add the mixed impregnation solution and tetraethyl silicate dropwise onto the pseudo-boehmite (wherein the weight ratio of the main active metal component precursor: the auxiliary active metal component precursor: the silicon modified component precursor: the water: the alumina precursor is 0.35:0.23:0.41:3.2:1), stir vigorously for 2h to mix evenly, age at 10℃ in air atmosphere for 12h, and then dry at 100℃ for 8h to obtain a catalyst semi-finished product;
[0083] (2) The semi-finished catalyst was uniformly mixed with 0.4 g of Tianqing powder, 0.2 g of nitric acid, 0.2 g of citric acid, and an appropriate amount of deionized water, and extruded into a clover-shaped catalyst with a diameter of 1.5 mm. The resulting clover-shaped catalyst was dried at 80°C for 12 h, calcined at 500°C in a 15% O2 / N2 atmosphere for 4 h, and naturally cooled to obtain the silicon-modified hydrorefining catalyst, designated SC-1.
[0084] It was measured that in the SC-1 catalyst, the total content of tungsten oxide and nickel oxide was 31.0 weight % based on the total weight of the catalyst, of which the content of tungsten oxide as the main active metal component was 26.0 weight %, the content of nickel oxide as the auxiliary active metal component was 5.0 weight %, and the content of the silicon-modified component was 10.0 weight %.
[0085] The SEM image of the catalyst SC-1 is shown in Figure 1 As shown by Figure 1 It can be seen that the catalyst SC-1 prepared in this example has a "surface microsphere structure".
[0086] Comparative Example 1
[0087] (1) Dissolve 6.05 g of ammonium metatungstate and 3.89 g of nickel nitrate in 64.00 g of deionized water to prepare a mixed impregnation solution. Separately, take 20.00 g of pseudo-boehmite for later use. Add the mixed impregnation solution dropwise onto the pseudo-boehmite, vigorously stir for 2 h to mix evenly, age naturally for 12 h, and then dry at 100° C. for 8 h to obtain a catalyst semi-finished product.
[0088] (2) The semi-finished catalyst was uniformly mixed with 0.4 g of Tianqing powder, 0.2 g of nitric acid, 0.2 g of citric acid, and an appropriate amount of deionized water, and extruded into a clover-shaped catalyst with a diameter of 1.5 mm. The resulting clover-shaped catalyst was dried at 80°C for 12 h, calcined at 500°C in a 15% O2 / N2 atmosphere for 4 h, and naturally cooled to obtain the silicon-modified hydrorefining catalyst, designated D-1.
[0089] It was determined that the total content of nickel oxide and tungsten oxide in the D-1 catalyst was 31.0 wt %, based on the total weight of the catalyst, of which the content of tungsten oxide was 26.0 wt % and the content of nickel oxide was 5.0 wt %.
[0090] Example 2
[0091] (1) Take 4.41g of ammonium molybdate and 6.21g of cobalt nitrate and dissolve them in 54.72g of deionized water to prepare a mixed impregnation solution. Take 16.03g of tetrabutyl silicate and 17.10g of pseudo-boehmite for later use. Add the mixed impregnation solution and isopropyl silicate dropwise onto the pseudo-boehmite (wherein the weight ratio of the main active metal component precursor: the auxiliary active metal component precursor: the silicon modified component precursor: the water: the alumina precursor is 0.26:0.36:0.94:1), stir vigorously for 2h to mix evenly, age at 20℃ in air atmosphere for 16h, and then dry at 110℃ for 6h to obtain a catalyst semi-finished product;
[0092] (2) The above-mentioned semi-finished catalyst was uniformly mixed with 0.4 g of polyethylene glycol, 0.2 g of nitric acid, 0.3 g of citric acid, and an appropriate amount of deionized water, and extruded into a catalyst strip having a diameter of 1.5 mm. The resulting catalyst strip was dried at 120° C. for 7 h, calcined at 500° C. in air for 4 h, and naturally cooled to obtain the silicon-modified hydrorefining catalyst, designated SC-2.
[0093] The total content of molybdenum oxide and cobalt oxide in the SC-2 catalyst was measured to be 26.0 wt % based on the total weight of the catalyst, of which the content of molybdenum oxide was 18.0 wt %, the content of cobalt oxide was 8.0 wt %, and the content of silicon-modified components was 15.0 wt %.
[0094] Comparative Example 2
[0095] (1) Dissolve 4.41 g of ammonium molybdate and 6.21 g of cobalt nitrate in 68.64 g of deionized water to prepare a mixed impregnation solution. Separately, take 21.45 g of pseudo-boehmite for later use. Add the mixed impregnation solution dropwise onto the pseudo-boehmite, stir vigorously for 2 h to mix evenly, age naturally for 16 h, and then dry at 110° C. for 6 h to obtain a catalyst semi-finished product.
[0096] (2) The above-mentioned semi-finished catalyst was uniformly mixed with 0.4 g of polyethylene glycol, 0.2 g of nitric acid, 0.3 g of citric acid, and an appropriate amount of deionized water, and extruded into a catalyst strip with a diameter of 1.5 mm. The resulting catalyst strip was dried at 120° C. for 7 h, then calcined at 500° C. in air for 4 h, and naturally cooled to obtain the silicon-modified hydrorefining catalyst, designated D-2.
[0097] It was determined that the total content of molybdenum oxide and cobalt oxide in the D-2 catalyst was 26.0 wt % based on the total weight of the catalyst, of which the content of molybdenum oxide was 18.0 wt % and the content of cobalt oxide was 8.0 wt %.
[0098] Example 3
[0099] (1) Take 2.45g of ammonium molybdate, 3.72g of ammonium metatungstate and 7.01g of nickel nitrate and dissolve them in 49.16g of deionized water to prepare a mixed impregnation solution. Take another 10.58g of propyl orthosilicate and 15.36g of pseudo-boehmite for later use. Add the mixed impregnation solution and propyl orthosilicate dropwise onto the pseudo-boehmite (wherein the weight ratio of the main active metal component precursor: the auxiliary active metal component precursor: the silicon modified component precursor: the water: the alumina precursor is 0.40:0.46:0.69:3.2:1), stir vigorously for 2h to mix evenly, age at 20℃ in air atmosphere for 15h, and then dry at 120℃ for 6h to obtain a catalyst semi-finished product;
[0100] (2) The catalyst powder was uniformly mixed with 0.4 g of methyl cellulose, 0.2 g of nitric acid, 0.2 g of tartaric acid, and an appropriate amount of deionized water, and extruded into catalyst pellets with a diameter of 1.5 mm. The resulting catalyst pellets were dried at 80°C for 15 h, calcined at 450°C in air for 4 h, and naturally cooled to obtain the silicon-modified hydrorefining catalyst, designated SC-3.
[0101] It was measured that in the SC-3 catalyst, based on the total weight of the catalyst, the total content of molybdenum oxide, tungsten oxide and nickel oxide was 35.0 weight%, of which the content of molybdenum oxide was 10.0 weight%, the content of tungsten oxide was 16.0 weight%, and the content of nickel oxide was 9.0 weight%; the content of silicon-modified components was 12.0 weight%.
[0102] Comparative Example 3
[0103] (1) Dissolve 2.45 g of ammonium molybdate, 3.72 g of ammonium metatungstate, and 7.01 g of nickel nitrate in 60.29 g of deionized water to prepare a mixed impregnation solution. Separately, take 18.84 g of pseudo-boehmite for later use. Add the mixed impregnation solution dropwise onto the pseudo-boehmite, vigorously stir for 2 h to mix evenly, age naturally for 15 h, and then dry at 120° C. for 6 h to obtain a semi-finished catalyst.
[0104] (2) The semi-finished catalyst was uniformly mixed with 0.4 g of methyl cellulose, 0.2 g of nitric acid, 0.2 g of tartaric acid, and an appropriate amount of deionized water, and extruded into catalyst pellets with a diameter of 1.5 mm. The resulting catalyst pellets were dried at 80°C for 15 h, calcined at 450°C in air for 4 h, and naturally cooled to obtain the silicon-modified hydrorefining catalyst, designated D-3.
[0105] It was measured that the total content of nickel oxide, molybdenum oxide and tungsten oxide in the D-3 catalyst was 35.0 weight % based on the total weight of the catalyst, of which the content of molybdenum oxide was 10.0 weight %, the content of tungsten oxide was 16.0 weight % and the content of nickel oxide was 9.0 weight %.
[0106] Comparative Example 4
[0107] This comparative example refers to the preparation method of Example 1, and the difference from Example 1 is that the amount of raw materials added is changed, specifically including:
[0108] (1) Take 2.79g of ammonium metatungstate and 0.78g of nickel nitrate and dissolve them in 43.59g of deionized water to prepare a mixed impregnation solution. Take another 27.78g of tetraethyl silicate and 13.62g of pseudo-boehmite for later use. Add the mixed impregnation solution and tetraethyl silicate dropwise onto the pseudo-boehmite (wherein the weight ratio of the main active metal component precursor: the auxiliary active metal component precursor: the silicon modified component precursor: the water: the alumina precursor is 0.20:0.06:2.04:3.2:1), stir vigorously for 2h to mix evenly, age at 10℃ in air atmosphere for 12h, and then dry at 100℃ for 8h to obtain a catalyst semi-finished product;
[0109] (2) The semi-finished catalyst was uniformly mixed with 0.4 g of Tianqing powder, 0.2 g of nitric acid, 0.2 g of citric acid, and an appropriate amount of deionized water, and extruded into a clover-shaped catalyst with a diameter of 1.5 mm. The resulting clover-shaped catalyst was dried at 80°C for 12 h, calcined at 500°C in a 15% O2 / N2 atmosphere for 4 h, and naturally cooled to obtain the silicon-modified hydrorefining catalyst, designated SC-4.
[0110] It was measured that in the SC-4 catalyst, the total content of tungsten oxide and nickel oxide was 13.0 weight % based on the total weight of the catalyst, of which the content of tungsten oxide as the main active metal component was 12.0 weight %, the content of nickel oxide as the auxiliary active metal component was 1.0 weight %, and the content of the silicon-modified component was 40.0 weight %.
[0111] Example 5
[0112] This example refers to the preparation method of Example 1, and the difference from Example 1 is that the preparation conditions are changed, specifically including:
[0113] (1) Take 6.05g of ammonium metatungstate and 3.89g of nickel nitrate and dissolve them in 54.72g of deionized water to prepare a mixed impregnation solution. Take another 6.94g of tetraethyl silicate and 17.10g of pseudo-boehmite for later use. Add the mixed impregnation solution and tetraethyl silicate dropwise onto the pseudo-boehmite (wherein the weight ratio of the main active metal component precursor: the auxiliary active metal component precursor: the silicon modified component precursor: the water: the alumina precursor is 0.35:0.23:0.41:3.2:1), stir vigorously for 3h to mix evenly, age at 100℃ in air atmosphere for 6h, and then dry at 60℃ for 3h to obtain a catalyst semi-finished product;
[0114] (2) The semi-finished catalyst was uniformly mixed with 0.4 g of Tianqing powder, 0.2 g of nitric acid, 0.2 g of citric acid, and an appropriate amount of deionized water, and extruded into a clover-shaped catalyst with a diameter of 1.5 mm. The resulting clover-shaped catalyst was dried at 50°C for 3 h, calcined at 900°C in a 15% O2 / N2 atmosphere for 5 h, and naturally cooled to obtain the silicon-modified hydrorefining catalyst, designated SC-5.
[0115] It was measured that in the SC-5 catalyst, the total content of tungsten oxide and nickel oxide was 31.0 weight % based on the total weight of the catalyst, of which the content of tungsten oxide as the main active metal component was 26.0 weight %, the content of nickel oxide as the auxiliary active metal component was 5.0 weight %, and the content of the silicon-modified component was 10.0 weight %.
[0116] The BET specific surface area, total pore volume, total acid content determined by 150°C pyridine infrared, The acid content data are listed in the following Table 1. The component contents of the catalyst products obtained in Examples and Comparative Examples are listed in the following Table 2.
[0117] Table 1
[0118]
[0119] In Table 1, no silicon element was introduced into Comparative Examples 1 to 3, and they did not contain B acid, and the symbol "——" indicates that it does not exist.
[0120] Table 2
[0121]
[0122]
[0123] Reaction Test Example 1
[0124] This test example provides a test experiment of hydrogenating coked diesel using the catalysts prepared in the above examples and comparative examples.
[0125] The catalyst of the embodiment and the comparative example catalyst were compared respectively, and the reaction process was as follows: presulfurization was carried out before application to make the catalyst have better hydrogenation effect. Presulfurization was carried out using a 10mL high temperature and high pressure hydrogenation micro-reaction device. It was a wet in-situ presulfurization, i.e., wet presulfurization was used. After presulfurization, the catalyst was not unloaded, and hydrogenation reaction was continued directly in the reactor. The presulfurized oil was a n-decane solution containing 5 wt% CS2, and the presulfurization temperature was 320°C, the pressure was 4MPa, and the liquid hourly mass space velocity was 1.5h -1 , the hydrogen-to-oil volume ratio is 300.
[0126] The hydrotreatment of this test example was carried out using a 10mL high temperature and high pressure hydrotreatment microreactor. The raw material used for evaluation was Daqing coking diesel, which has a specific gravity (d4 20 ) was 0.8274, the sulfur content was 1067ppm, and the total nitrogen content was 883ppm. The raw materials were pumped in by a plunger pump. The oil sample after reaction was cooled in the high separator and collected and analyzed in the low separator. The temperature of the hydrotreating was 300℃, the pressure was 4MPa, and the liquid hourly mass space velocity was 3.0h -1 The hydrogen-to-oil volume ratio was 500. The evaluation results of the hydrogenation catalyst are shown in Table 3.
[0127] The sulfur and nitrogen contents of the reactants and products were detected by ultraviolet fluorescence and chemiluminescence detection methods.
[0128] Desulfurization rate (mol%) = (raw material sulfur content - product sulfur content) / raw material sulfur content × 100%;
[0129] Denitrification rate (mol %) = (nitrogen content of raw material - nitrogen content of product) / nitrogen content of raw material × 100%.
[0130] Table 3
[0131] catalyst Desulfurization rate, mole % Denitrification rate, mole % SC-1 95 88 D-1 89 82 SC-2 94 86 D-2 87 82 SC-3 97 92 D-3 91 85 SC-4 65 55 SC-5 77 60
[0132] According to the data in Table 3 above, we can see that:
[0133] Comparing Example 1 with Comparative Example 1, Example 2 with Comparative Example 2, and Example 3 with Comparative Example 3, the silicon-modified hydrorefining catalysts containing silicon element prepared in Examples 1 to 3 have a higher catalytic effect in the hydrotreating reaction of coked diesel, and can achieve higher desulfurization and denitrification rates;
[0134] Comparing Example 1 with Comparative Example 4, it can be seen that the raw material addition ratio in the preparation process of Comparative Example 4 is not within the ratio range provided in the present disclosure, and the component content of the prepared catalyst SC-4 is also not within the range of "15-40 weight% of the main active metal component, 2-12 weight% of the auxiliary active metal component, 5-20 weight% of the silicon-modified component and 45-70 weight% of the carrier". The desulfurization rate of the catalyst SC-4 in the hydrotreating reaction of coked diesel is only 65 mol%, and the denitrification rate is only 55 mol%. The catalyst SC-1 prepared in Example 1 has a better catalytic effect and has higher desulfurization and denitrification rates.
[0135] Comparing Example 1 with Example 5, it can be seen that the preparation conditions of Example 5 are not within the scope of the conditions provided in the present disclosure. The catalyst SC-5 obtained in Example 5 has a desulfurization rate of only 77 mol% and a denitrification rate of only 60 mol% in the reaction of hydrotreating coked diesel. The catalyst SC-1 prepared in Example 1 has a better catalytic effect and has higher desulfurization and denitrification rates.
[0136] Reaction Test Example 2
[0137] This test example provides a test experiment of hydrogenating catalytic cracking diesel using the catalysts prepared in the above examples and comparative examples.
[0138] The catalyst of the embodiment and the comparative example catalyst were compared respectively, and the reaction process was as follows: presulfurization was carried out before application to make the catalyst have better hydrogenation effect. Presulfurization was carried out using a 10mL high temperature and high pressure hydrogenation micro-reaction device. It was a wet in-situ presulfurization, i.e., wet presulfurization was used. After presulfurization, the catalyst was not unloaded, and hydrogenation reaction was continued directly in the reactor. The presulfurized oil was a n-decane solution containing 5 wt% CS2, and the presulfurization temperature was 320°C, the pressure was 4MPa, and the liquid hourly mass space velocity was 1.5h -1 , the hydrogen-to-oil volume ratio is 300.
[0139] The hydrotreatment of this test case was carried out using a 10mL high temperature and high pressure hydrotreatment microreactor. The raw material used for evaluation was Daqing catalytic cracking diesel, the specific gravity of which (d4 20) is 0.8894, the sulfur content is 1178ppm, and the total nitrogen content is 915ppm. The raw materials are pumped in by a plunger pump. The oil sample after reaction is cooled in the high separator and collected and analyzed in the low separator. The temperature of the hydrotreating is 300℃, the pressure is 4MPa, and the liquid hourly space velocity is 4.0h -1 The hydrogen-to-oil volume ratio was 600. The evaluation results of the catalyst after hydrotreatment are shown in Table 4.
[0140] The sulfur and nitrogen contents of the reactants and products were detected by ultraviolet fluorescence and chemiluminescence detection methods.
[0141] Desulfurization rate (mol%) = (raw material sulfur content - product sulfur content) / raw material sulfur content × 100%;
[0142] Denitrification rate (mol %) = (nitrogen content of raw material - nitrogen content of product) / nitrogen content of raw material × 100%.
[0143] Table 4
[0144] catalyst Desulfurization rate, mole % Denitrification rate, mole % SC-1 93 88 D-1 85 83 SC-2 93 89 D-2 83 82 SC-3 96 92 D-3 87 84 SC-4 62 50 SC-5 76 63
[0145] According to the data in Table 4 above, we can see that:
[0146] Comparing Example 1 with Comparative Example 1, Example 2 with Comparative Example 2, and Example 3 with Comparative Example 3, the silicon-modified hydrorefining catalysts containing silicon element prepared in Examples 1 to 3 have a higher catalytic effect in the hydrotreating reaction of catalytic cracking diesel, and can achieve higher desulfurization and denitrification rates;
[0147] Comparing Example 1 with Comparative Example 4, it can be seen that the raw material addition ratio in the preparation process of Comparative Example 4 is not within the ratio range provided in the present disclosure, and the component content of the prepared catalyst SC-4 is also not within the range of "15-40 weight% of the main active metal component, 2-12 weight% of the auxiliary active metal component, 5-20 weight% of the silicon-modified component, and 45-70 weight% of the carrier". The desulfurization rate of the catalyst SC-4 in the hydrotreatment reaction of catalytically cracked diesel is only 62 mol%, and the denitrification rate is only 50 mol%. The catalyst SC-1 prepared in Example 1 has a better catalytic effect and has higher desulfurization and denitrification rates.
[0148] Comparing Example 1 with Example 5, it can be seen that the preparation conditions of Example 5 are not within the scope of the conditions provided in the present disclosure. The catalyst SC-5 obtained in Example 5 has a desulfurization rate of only 76 mol% and a denitrification rate of only 63 mol% in the hydrotreatment reaction of catalytic cracking diesel. The catalyst SC-1 prepared in Example 1 has a better catalytic effect and has higher desulfurization and denitrification rates.
[0149] The preferred embodiments of the present disclosure are described in detail above. However, the present disclosure is not limited to the specific details of the above embodiments. Within the technical concept of the present disclosure, various simple modifications can be made to the technical solutions of the present disclosure, and these simple modifications all fall within the scope of protection of the present disclosure.
[0150] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0151] In addition, the various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A silicon-modified hydrorefining catalyst, characterized in that: Based on the total weight of the silicon-modified hydrorefining catalyst, the silicon-modified hydrorefining catalyst comprises 15 to 40 weight percent of a main active metal component, 2 to 12 weight percent of an auxiliary active metal component, 5 to 20 weight percent of a silicon-modified component and 45 to 70 weight percent of a carrier; The main active metal component and the auxiliary active metal component are calculated in the form of metal oxides, and the silicon-modified component is calculated in the form of SiO2; the main active metal component is selected from one or more metal elements of Group VIB, and the auxiliary active metal component is selected from one or more metal elements of Group VIII; the carrier includes alumina.
2. The silicon-modified hydrorefining catalyst according to claim 1, characterized in that: The main active metal component includes oxides of one or two metal elements selected from Mo and W; the auxiliary active metal component includes oxides of one or two metal elements selected from Ni and Co.
3. The silicon-modified hydrorefining catalyst according to claim 1, characterized in that: The total acid content of the silicon-modified hydrorefining catalyst measured by pyridine infrared at 150°C is 120-160 μmol / g; Preferably, the silicon-modified hydrotreating catalyst comprises Acid centers and Lewis acid centers, among which Acid center content 2 to 15 μmol / g; further preferably, The ratio of acid center content to Lewis acid center content is 1:10 to 50; Optionally, the BET specific surface area of the silicon-modified hydrorefining catalyst is 200 to 300 m 2 / g, pore volume is 0.3~0.5cm 3 / g.
4. A method for preparing a silicon-modified hydrorefining catalyst, characterized in that: The following steps are involved: S1, mixing a main active metal component precursor, an auxiliary active metal component precursor, a silicon modified component precursor, water and an alumina precursor, and performing an aging treatment to obtain a catalyst intermediate; The metal element of the main active metal component precursor is selected from one or more metal elements of Group VIB, the metal element of the auxiliary active metal component precursor is selected from one or more metal elements of Group VIII, and the silicon-modified component precursor is selected from one or more hydrolyzable silicon-containing compounds; S2, mixing the catalyst intermediate with a molding aid, and performing molding and calcining treatments.
5. The method according to claim 4, characterized in that In step S1, the main active metal component precursor: the auxiliary active metal component precursor: the silicon modified component precursor: The weight ratio of water:aluminum oxide precursor is 0.1-2:0.02-1.5:0.1-3:1-4:1; preferably 0.15-0.8:0.05-0.7:0.15-1.0:2-3.5:
1.
6. The method according to claim 4, characterized in that The main active metal component precursor is selected from one or more of a molybdenum metal precursor and a tungsten metal precursor; preferably, the molybdenum metal precursor is selected from one or more of sodium molybdate, ammonium molybdate, molybdenum chloride and molybdic acid, preferably ammonium molybdate; the tungsten metal precursor is selected from one or more of ammonium metatungstate, phosphotungstic acid and silicotungstic acid, preferably ammonium metatungstate and / or phosphotungstic acid; The auxiliary active metal component precursor is selected from one or more of a nickel metal precursor and a cobalt metal precursor; preferably, the nickel metal precursor is selected from one or more of nickel nitrate, basic nickel carbonate and nickel sulfate, preferably basic nickel carbonate and / or nickel nitrate; the cobalt metal precursor is selected from one or more of cobalt sulfate, cobalt carbonate, cobalt oxalate and cobalt nitrate, preferably cobalt nitrate and / or cobalt oxalate; The silicon-modified component precursor is selected from one or more of silicon tetrachloride, methyl silicate, silicon acetate, tetraethyl silicate, propyl orthosilicate, tetraisopropyl orthosilicate and tetrabutyl silicate; preferably selected from one or more of tetraethyl silicate, propyl orthosilicate and tetrabutyl silicate. The aluminum oxide precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide and aluminum nitrate; preferably pseudo-boehmite.
7. The method according to claim 4, characterized in that In step S1, the aging treatment conditions include: aging at 0-40°C for 15-30h; Optionally, the method further comprises: drying the product obtained by the aging treatment at 80 to 160° C. for 4 to 12 hours.
8. The method according to claim 4, characterized in that In step S2, the calcination treatment conditions include: calcination at 300-700°C for 3-10 hours; the calcination atmosphere is one or more of air, nitrogen, oxygen, argon and water vapor; Optionally, before the calcination treatment, the product obtained by the molding treatment is dried at 80 to 160° C. for 4 to 12 hours.
9. The silicon-modified hydrorefining catalyst prepared according to the method according to any one of claims 4 to 8.
10. Use of the silicon-modified hydrotreating catalyst according to any one of claims 1 to 3 and claim 9 in a crude oil hydrotreating reaction.
11. The use according to claim 10, characterized in that: The crude oil hydrofining reaction comprises the following steps: Under hydrogenation conditions, the crude oil is brought into contact with the silicon-modified hydrotreating catalyst to perform a hydrotreating reaction; Optionally, the conditions of the hydrofining reaction include: reaction temperature of 260-380°C; hydrogen pressure of 4-10 MPa; hydrogen-oil volume ratio of 300-800:1; feed oil mass space velocity of 0.5-6h -1 ; Optionally, the feedstock oil is selected from gasoline and / or diesel fractions; Preferably, the feedstock oil hydrotreating reaction further comprises the following step: performing a sulfurization treatment on the silicon-modified hydrotreating catalyst before carrying out the hydrotreating reaction.
Citation Information
Patent Citations
Hydrotreatment catalyst and preparation method thereof
CN102319572A
Catalytic cracking catalyst and preparation method thereof
CN104014361A
Catalyst for preparing glycolate through hydrogenating oxalate, preparation method for catalyst and use of catalyst
CN105582915A
Fischer-Tropsch oil hydrofining catalyst, preparation method and application of Fischer-Tropsch oil hydrofining catalyst and Fischer-Tropsch oil hydrofining method
CN105772011A
Hydrorefining catalyst for oil product, and preparation method and application thereof
CN106914260A